Dr. Lilith Ritter and the Femme Fatale Archetype in Nightmare Alley (2021): A Sociological Perspective - Azizah Nur Rahmadhani; Ali Mustofa (Universitas Islam Negeri Palopo, 2026)
This study examines how Dr. Lilith Ritter in Guillermo del Toro's Nightmare Alley (2021) subverts the traditional femme fatale archetype through intellectual rather than sexual power. Applying Yvonne Tasker's (1993) sociological framework of the